Astonishing insights: emerging market debt spreads throughout the pandemic. Issue 18 (15th April 2022) - Gubareva, Mariya; Umar, Zaghum; Sokolova, Tatiana; Vo, Xuan Vinh
ABSTRACT: We investigate how Covid-19 affects the emerging market (EM) bonds by analysing, on a standalone basis, investment grade (IG) and high yield (HY) debt per type of issuer. We document evidence that the option-adjusted spreads (OAS) of the IG and HY financials have recovered to the pre-Covid levels by the end of year 2020, while for the HY sovereigns and corporates the OAS remain twice as wide as before the pandemic. The weight of the liquidity component in the OAS for the IG sovereigns has climbed to astonishing 45%. Our results are potentially useful for investors, traders, risk managers and regulators.